Asymmetric right ventricular myocardial work correlates with gold standard measurements of cardiac function in pulmonary hypertension - Simone G. Diab; Ryota Ebata; Dariusz Mroczek; Wei Hui; Espen W. Remme; Thomas Möller; Mark K. Friedberg (Pulmonary Circulation)
Abstract Right ventricular (RV) (dys)function determines outcomes in pulmonary hypertension (PH). We previously found that asymmetric RV myocardial work (MW) corresponds with inefficient RV function in experimental PH models. We therefore aimed to investigate regional distribution of RV MW and its correlation with catheter hemodynamics in children with PH. RV MW was calculated by longitudinal strain and simultaneous catheter pressure measurements in 14 patients with PH. Wasted MW was defined as the ratio of inappropriate myocardial lengthening to favorable shortening work. Segment‐wise and averaged MW and wasted MW were evaluated at baseline and during pulmonary vasodilation therapy with oxygen and nitric oxide, and their relationship to hemodynamic measurements was analyzed. We found that MW was higher for the lateral wall than the septum: 1013 ± 374 mmHg · % versus 532 ± 190 mmHg · % at baseline. Wasted MW ratio did not differ significantly between wall regions. Pulmonary vasodilators slightly reduced mean pulmonary artery pressure and was accompanied by a more symmetrical MW distribution. Averaged MW correlated with the rate of RV pressure development (dP/dt maximum) and decay (dP/dt minimum) at all conditions (p  ≤ 0.047). The results suggest that MW contribute to, and may be used as a marker of, systolic and diastolic efficiency in the PH RV.